Cycling in the heat: performance perspectives and cerebral challenges - Nybo, L. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Cycling performances require periods with high power output and consequently large endogenous heat production. During cycling in temperate or cold climates, heat is mainly released from the skin to the surroundings via convection, whereas evaporative heat loss becomes the dominant or only mechanism for heat dissipation when the environmental temperature increases. Accordingly, large sweat rates are required, which may challenge the cyclists' electrolyte and water balance. Furthermore, the cooling capacity of the environment may become a limiting factor for the ability to maintain heat balance, for example during cycling in very humid climates or when cycling up-hill as the wind speed decreases and reduces the maximal rate of evaporative heat loss. Hyperthermia may in itself hamper performance, but especially in combination with dehydration it may deteriorate the cyclist's ability to maintain power output. Fatigue mechanisms involve cardiovascular stressing, but it also appears that factors within the central nervous system are of major importance for motor performance during such exercise. However, the influence of the environmental temperature on cycling performance appears to vary markedly depending on the course, the air humidity and the cyclist ability to avoid dehydration. If hyperthermia becomes a major issue, it will deteriorate performance, but as long as temperature and water balance can be established, the high air temperature may actually benefit performance because air density and air resistance will decrease and lower the power output required to maintain a given velocity.